Analysis Of Figurative Language Used In Poem Written By Emily Dickinson - Remigius Astanjo; I Made Juliarta; I Putu Eka Suardana (Universitas Bali Dwipa, 2025)
This research aims to explore the use of figurative language in Emily Dickinson's poems through a theoretical study approach, providing new insights into the aesthetic richness and meaning of these classic literary works. The study analyzes various types of figurative language in Dickinson's poetry, specifically focusing on simile, metaphor, personification, paradox, and hyperbole. A qualitative research method is employed, with data collected from books and online sources related to literature and poetry. The researcher examines Dickinson’s poems by reading, identifying, understanding, and drawing conclusions about the use of figurative language. The findings indicate that figurative language in Dickinson’s poetry plays a crucial role in engaging readers, prompting them to think and imagine deeply. Additionally, the historical context and biography of the poet offer valuable insights into how literary works reflect and respond to both social and personal circumstances. The study also recommends conducting comparative research between Dickinson’s poetry and that of other female poets from the same period or those with similar literary styles. These recommendations aim to guide students, researchers, and academic institutions in studying literature, particularly in understanding how language is used to convey ideas and create a distinctive literary experience for readers.